Mapping the effect of paddy field to total suspended solid - Nur Nadia Sidi Omar (School of Environmental Engineering, University Malaysia Perlis, 2012)
Perlis is one of the states that most of the landuse is paddy field. The objectives of this study are to determine the impact of paddy field that changes the concentration of Total Suspended Solid (TSS), to analyze TSS on several rivers in Perlis, and to map the landuse of paddy field. Landuse of paddy field is one of the factors that effect the TSS. There are several reasons that causes the concentration of TSS change includes weather, water velocity and activities on the paddy filed. The rivers that involve are Temenggong River, Panggas Kechil River, Jerneh River, Ngolang River, Siran River, Kok Kelang River, Alur Redis River and Arau River. Only once a week the sampling was done cover wet season and dry season. In - situ parameters include river width, river depth, water temperature and water velocity. Range of river width is between 3.71 m to 27.8 m and the depth ranges is between 0.1 m to 4.3 m. Water temperature is almost similar for all the sampling location. The temperatures are between 26C to 30C. Water velocities for the entire rivers have a range between 0.77 m/s to 2.606 m/s. Range of turbidity is between 3.89 NTU to 678 NTU while the range of TSS is between 2 mg/L to 85 mg/L. Finally, the landuse map was generated.